Analisis Kemampuan Berpikir Kritis Matematika Siswa SMA - Mujahid, Nurhakimah; Ruslan; Thalib, Ahmad (Issues in Mathematics Education (IMED), 2018)
Mathematical thinking ability, particularly the high level of mathematical thinking (high-order mathematical thinking) badly needed by students in order to make students able to confront changes in circumstances or challenges they have in life is always developing. This study aims to describe the mathematical analysis of the critical thinking ability of students in SMA Negeri 5 Wajo.This research was qualitative with the descriptive approach. The subject in this study using a XII IPA 1 grade in SMA Negeri 5 Wajo reviewed from an initial capability that add up to 3 people. The subject is taken using the test ability early, then the subject is given a test of mathematical and critical thinking abilities were interviewed. Test data of mathematical and critical thinking abilities interview each of the subject is described.On the analysis of the data it can be concluded that the ability of critical thinking, analysis of the mathematical ability of students beginning by using Graded Response Model (GRM) noted that the ability of the initial of the high, medium and low indicating the same mathematics critical thinking ability in stages an average between 1,00 to -1,00